Experimental platform for collaborative inter and intra cellular fuzzy scheduling in an ubiquitous manufacturing system - Varela, M.L.R. (2012)
The aim of manufacturing scheduling is the efficient allocation of machines and other resources to jobs, or operations within jobs, and the subsequent time phasing of these jobs on individual machines. Therefore, the scheduling of production processes of a distributed cellular manufacturing enterprise is one of the significant tasks to be performed to achieve competitive production, which means, e.g., to deliver products on time or to use resources efficiently and reduce production times. In this paper we propose a Web Platform for solving those kind of problems occurring either in intra or inter cellular manufacturing scenarios. Scheduling methods are local or remotely available through web services and can be easily and continuously incorporated in a distributed repository, which integrates XML-based components, belonging to a range of business partners, integrating a Virtual Enterprise, in the context of an Ubiquitous Manufacturing System. The scheduling data modeling and the data transferring processes are based on XML and related web technologies and decision-making is carried out through an interactive approach relying on fuzzy sets and user friendly interfaces for supporting cellular manufacturing scheduling.